2012
DOI: 10.1530/joe-12-0030
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor activation following elevated oocyte cortisol content is associated with zygote activation, early embryo cell division, and IGF system gene responses in rainbow trout

Abstract: Increased in ovo cortisol content of rainbow trout oocytes from w3 . 5 to w5 . 0 ng.oocyte K1 before fertilization enhances the growth of embryos and juveniles and changes the long-term expression pattern of IGF-related genes. This study used embryos reared from oocytes enriched with cortisol and the glucocorticoid receptor (GR) antagonist, RU486, to determine whether the growth-promoting actions of cortisol involve GR protein activation and modulation of gr expression. Whole-mount in situ immunohistofluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…Another possibility is that the receptor activity is controlled by cofactors like the ipo7 transcript, which encodes a protein essential for the transport of the glucocorticoid receptor into the nucleus, where cortisol exerts its functions. Interestingly, it was recently observed that elevated cortisol content in rainbow trout oocytes activates the glucocorticoid receptor, leading to increased cell division in early blastula (Li et al, 2012b), which further supports our finding that elevated cortisol increases the expression of ipo7 and also affects many cytogenesis related factors. It is known that individual fish might be high and low responders to stress (Fevolden et al, 1991;Fevolden et al, 2002;Fevolden et al, 2003).…”
Section: Genes Differentially Expressed In Maternal Stagessupporting
confidence: 91%
See 3 more Smart Citations
“…Another possibility is that the receptor activity is controlled by cofactors like the ipo7 transcript, which encodes a protein essential for the transport of the glucocorticoid receptor into the nucleus, where cortisol exerts its functions. Interestingly, it was recently observed that elevated cortisol content in rainbow trout oocytes activates the glucocorticoid receptor, leading to increased cell division in early blastula (Li et al, 2012b), which further supports our finding that elevated cortisol increases the expression of ipo7 and also affects many cytogenesis related factors. It is known that individual fish might be high and low responders to stress (Fevolden et al, 1991;Fevolden et al, 2002;Fevolden et al, 2003).…”
Section: Genes Differentially Expressed In Maternal Stagessupporting
confidence: 91%
“…In agreement with this finding, extracellular region was also overrepresented among differentially expressed genes in liver of rainbow trout subjected to long term confinement stress (Cairns et al, 2008). Also Li et al (2012b) recently showed that cell division is increased in rainbow trout eggs containing elevated levels of cortisol. Some of the overrepresented biological processes identified in this study have previously been related to stress, and wound healing and likewise several of these were also found to be affected in salmon skin by cortisol implants (Krasnov et al, 2012).…”
Section: Genes Differentially Expressed In Maternal Stagessupporting
confidence: 80%
See 2 more Smart Citations
“…Maternal cortisol plays an important organizational role during early development in fish, and cortisol treatment of eggs or embryos alters both physiology and behaviour of the developing young (e.g. Sloman, 2010;Burton et al, 2011;Li et al, 2012;Nesan and Vijayan, 2012;Colson et al, 2015;. However, programming of offspring is probably more complex than the action of cortisol alone, because previous studies have found effects of maternal stress even in the absence of increased embryo cortisol levels -for example, on egg size in Neolamprologus pulcher (Mileva et al, 2011) and on swim performance in Oncorhynchus nerka (Sopinka et al, 2014).…”
Section: Introductionmentioning
confidence: 99%